2020
DOI: 10.1080/01443410.2020.1732874
|View full text |Cite
|
Sign up to set email alerts
|

Reading habits and emotional vocabulary in adolescents

Abstract: Previous research has found that reading increases overall vocabulary size, and that reading fiction, specifically, is associated with higher levels of empathy and better perspective-taking skills. The current study investigated a potential link between reading habits and emotional vocabulary in particular, to assess whether the link between reading and empathy could be specifically related to emotion words. A total of 415 Swedish secondary and upper secondary school students were asked to generate words in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
3
11
0
6
Order By: Relevance
“…The same effect is also found in the emotions comprehension in preschool ) and primary school (Beck et al, 2012;Kumschick et al, 2014;Lysaker & Tonge, 2013), with a stable effect in follow-up (Ornaghi et al, 2014). Emotional vocabulary is also increasing as a result of reading practice (Dylman et al, 2020;Kumschick et al, 2014;Ornaghi et al, 2014). Parents' socio-emotional discourses evaluated in conversations during and after reading in the family have an impact on children's understanding of the causes of emotions (Schapira & Aram, 2019).…”
Section: Reading and Emotional Knowledgementioning
confidence: 55%
See 2 more Smart Citations
“…The same effect is also found in the emotions comprehension in preschool ) and primary school (Beck et al, 2012;Kumschick et al, 2014;Lysaker & Tonge, 2013), with a stable effect in follow-up (Ornaghi et al, 2014). Emotional vocabulary is also increasing as a result of reading practice (Dylman et al, 2020;Kumschick et al, 2014;Ornaghi et al, 2014). Parents' socio-emotional discourses evaluated in conversations during and after reading in the family have an impact on children's understanding of the causes of emotions (Schapira & Aram, 2019).…”
Section: Reading and Emotional Knowledgementioning
confidence: 55%
“…Chisholm, Shelton, & Sheffield, 2017). One of these latter studies followed the sample till the last years of high school (Dylman, Blomqvist, & Champoux-Larsson, 2020). 5 studies focused on high school participants (e.g.…”
Section: School-agementioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, underlying vocabulary knowledge might be used to compensate for difficulties in word retrieval (Gordon et al, 2018). A related finding is that reading and writing habits, which are per se linked with vocabulary (Stanovich and Cunningham, 1992;Marulis and Neuman, 2010;Dylman et al, 2020), seem to be associated with VF performance in both cognitively healthy adults (Pawlowski et al, 2012) and patients with AD (Tessaro et al, 2020). In at least non-clinical participants, the effect seems to be even more stronger than education (Pawlowski et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fernández-Berrocal, Cabello, Castillo and Extremera [ 39 ] believe that gender differences are mediated by age; therefore, we should be cautious when concluding that gender is a determining variable in EI, unless we have thoroughly analyzed the potential interaction with other variables. Dylman et al [ 40 ] found that girls produced more emotion words than boys in the vocabulary emotion task, and this may be connected to the finding that girls generally express their emotions more than boys (e.g., [ 41 ]).…”
Section: Discussionmentioning
confidence: 99%